Infancias, escuela y trama afectiva. Hacia la construcción de una episteme integral - Nudelman, Silvia (2024)
Childhood as a social construct of modernity constitutes an object of study in different fields of Social Sciences, but also an object of political-pedagogical intervention. The purpose of this article is to elaborate interdisciplinary intersections around the relationship between education, school, and childhood. From its beginnings, the educational institution dealt with the modeling of sensibilities and the disciplining of the bodies of boys and girls, contributing to the construction of a hegemonic infant subject. Currently, the processes of cultural transformation characterized by the consumer economy, the excessive rise of new technologies, the media and growing inequality produce new subjectivities, as well as various representations and discourses about these subjects. This theoretical reconstruction is carried out within the framework of a socio-educational research that aims to understand the emotional experiences that boys and girls build in primary schools located in contexts of social vulnerability in Misiones, Argentina.